Cannabidiol restores intestinal barrier dysfunction and inhibits the apoptotic process induced by Clostridium difficile toxin A in Caco-2 cells. Issue 8 (December 2017) - Gigli, Stefano; Seguella, Luisa; Pesce, Marcella; Bruzzese, Eugenia; D'Alessandro, Alessandra; Cuomo, Rosario; Steardo, Luca; Sarnelli, Giovanni; Esposito, Giuseppe
Background: Clostridium difficile toxin A is responsible for colonic damage observed in infected patients. Drugs able to restore Clostridium difficile toxin A-induced toxicity have the potential to improve the recovery of infected patients. Cannabidiol is a non-psychotropic component of Cannabis sativa, which has been demonstrated to protect enterocytes against chemical and/or inflammatory damage and to restore intestinal mucosa integrity. Objective: The purpose of this study was to evaluate (a) the anti-apoptotic effect and (b) the mechanisms by which cannabidiol protects mucosal integrity in Caco-2 cells exposed to Clostridium difficile toxin A. Methods: Caco-2 cells were exposed to Clostridium difficile toxin A (30 ng/ml), with or without cannabidiol (10 −7 –10 −9 M), in the presence of the specific antagonist AM251 (10 −7 M). Cytotoxicity assay, transepithelial electrical resistence measurements, immunofluorescence analysis and immunoblot analysis were performed in the different experimental conditions. Results: Clostridium difficile toxin A significantly decreased Caco-2 cells' viability and reduced transepithelial electrical resistence values and RhoA guanosine triphosphate (GTP), bax, zonula occludens-1 and occludin protein expression, respectively. All these effects were significantly and concentration-dependently inhibited by cannabidiol, whose effects were completely abolished in the presence of the cannabinoid receptor type 1 (CB1) antagonist, AM251. Conclusions: Cannabidiol improved Clostridium difficile toxin A-induced damage in Caco-2 cells, by inhibiting the apoptotic process and restoring the intestinal barrier integrity, through the involvement of the CB1 receptor.